Integrated Depression Management: A Proposed Trial of a New Model of Care in a Low Vision Rehabilitation Setting. (October 2013) - Rees, Gwyneth; Mellor, David; Holloway, Edith E.; Sturrock, Bonnie A.; Hegel, Mark T.; Casten, Robin; Xie, Jing; Finkelstein, Eric; Lamoureux, Ecosse; Keeffe, Jill E.
Abstract Purpose: Depression is a common problem among people with visual impairment and contributes to functional decline. This article presents a study protocol to evaluate a new model of care for those patients with depressive symptoms in which psychological treatment is integrated into low vision rehabilitation services. Low vision staff will be trained to deliver "problem solving therapy for primary care" (PST-PC), an effective psychological treatment developed specifically for delivery by non-mental health care staff. PST-PC is delivered in 8 weekly telephone sessions of 30–45 minutes duration and 4 monthly maintenance sessions. We predict this new integrated model of care will significantly reduce depressive symptoms and improve the quality of life for people with visual impairment. Methods and Design: A randomized controlled trial of PST-PC will be implemented nationally across low vision rehabilitation services provided by Vision Australia. Clients who screen positive for depressive symptoms and meet study criteria will be randomized to receive PST-PC or usual care, consisting of a referral to their general practitioner for more detailed assessment and treatment. Outcome measures include depressive symptoms and behaviors, quality of life, coping and psychological adjustment to visual impairment. Masked assessments will take place pre- and post-intervention as well as at 6- and 12-month follow-up. Conclusion: We anticipate that this innovative service delivery model will lead to sustained improvements in clients' quality of life in a cost effective manner and provide an innovative service delivery model suitable for other health care areas in which depression is co-morbid.